Pengaruh citra merek, harga, kualitas produk dan kualitas pelayanan terhadap keputusan pembelian 5 merek teh kemasan botol pada konsumen Toko Torus Tigaraksa - Saudara Dedi Saputra; Ahmad Rasyiddin; Hurian Kamela (Universitas Tangerang Raya, 2023)
In line with economic developments, the level of business competition in the bottled tea beverage industry in Indonesia is now getting increasingly tighter, especially for companies that produce similar products. The research method used is descriptive and quantitative. Data collection used the questionnaire method which was measured using a Likert scale and processed using the SPSS 25 program. The sample in this study was 100 people with the simple random sampling method. To find out and analyze the effect of the independent variables on the dependent variable, multiple linear regression equations, the coefficient of determination, and partial and simultaneous hypothesis testing are used. Based on the results of research that has been carried out, it shows that there is an influence of the independent variable on the dependent variable, which from the partial t test results for brand image with a value of 81,157, price 2,917, product quality 3,082, service quality 9,594 and each significant value is smaller than 0, 05. So it can be concluded that partially both brand image, price, product quality and service quality have a positive and significant influence on purchasing decisions. While simultaneously the variables brand image, price, product quality and service quality together have a positive and significant effect on the purchasing decision variable.